2022
DOI: 10.1364/jocn.442968
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional colorless WDM-PON RoF system with large spurious free dynamic range

Abstract: A bidirectional colorless wavelength-division-multiplexed passive optical network radio over fiber system with a large spurious-free dynamic range (SFDR) is proposed. By separating the unmodulated optical carrier from the polarization multiplexed optical signal in the optical network unit, upstream wavelength reuse is realized. By adjusting the angle and phase difference between the orthogonal optical polarization modes, third-order intermodulation distortion (IMD3) suppression of the downstream link is realiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…proportional to the square of oscillation amplitude, so the four polarizations are converted to two optical amplitudes that are cos 2 22.5°(~0.85) and cos 2 67.5°(~0. 15). The decision level could be set at 0.5 to distinguish A/B from C/D.…”
Section: Multi-ary Polskmentioning
confidence: 99%
See 2 more Smart Citations
“…proportional to the square of oscillation amplitude, so the four polarizations are converted to two optical amplitudes that are cos 2 22.5°(~0.85) and cos 2 67.5°(~0. 15). The decision level could be set at 0.5 to distinguish A/B from C/D.…”
Section: Multi-ary Polskmentioning
confidence: 99%
“…Another way to achieve colorless ONUs is upstream remodulation. [15][16][17][18][19][20][21][22][23][24][25][26][27][28] The downstream signals of different wavelengths are wavelength division demultiplexed by the wavelength division demultiplexer in the remote node. In each ONU, part of the downstream signal is drawn out for upstream remodulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers discussed the phase imbalance of the mm-wave such as the bidirectional colorless WDM-PON RoF system, in this (Wang et al, 2022) study, the periodic power fading caused by dispersion has been solved by modifying the angles and phases of the signal. Another study (Zabala-Blanco, Campuzano, Aldaya, Castañón, & Vargas-Rosales, 2018) reported the impact of partial phase imbalance, it discussed that the phase imbalance and phase noise for optical signals cause a chromatic dispersion in ber progressively and then limited the maximum achievable range of the signal.…”
Section: Introductionmentioning
confidence: 99%
“…However, the modulation of the n WDM channels in the transmitter requires to use WDM filters [15], [16] or arrayed waveguide gratings (AWGs) [17] to select between the wavelengths. Thus, n optical branches are established.…”
Section: Introductionmentioning
confidence: 99%